2015
DOI: 10.1186/s12889-015-2229-9
|View full text |Cite
|
Sign up to set email alerts
|

Australian health care providers’ views on opt-out HIV testing

Abstract: BackgroundOpt-out HIV testing is a novel concept in Australia. In the opt-out approach, health care providers (HCPs) routinely test patients for HIV unless they explicitly decline or defer. Opt-out HIV testing is only performed with the patients’ consent, but pre-test counselling is abbreviated. Australian national testing guidelines do not currently recommend opt-out HIV testing for the general population. Non-traditional approaches to HIV testing (such as opt-out) could identify HIV infections and facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…35 According to a qualitative study on Australian healthcare providers' views on optout HIV testing, some participants questioned its significance for the general Australian population, due to a lack of evidence for efficacy in lower prevalence populations. 36 Therefore, it is suggested that this practice may only be appropriate in areas with a high prevalence of HIV and sound promotion of PMTCT like Guangxi.…”
Section: Opt-out Modelmentioning
confidence: 99%
“…35 According to a qualitative study on Australian healthcare providers' views on optout HIV testing, some participants questioned its significance for the general Australian population, due to a lack of evidence for efficacy in lower prevalence populations. 36 Therefore, it is suggested that this practice may only be appropriate in areas with a high prevalence of HIV and sound promotion of PMTCT like Guangxi.…”
Section: Opt-out Modelmentioning
confidence: 99%
“…Our previous study of Australian healthcare provider views on opt-out HIV testing identified a subset of healthcare providers who thought that it was not feasible or acceptable (Leidel et al 2015). This study demonstrated that the opt-out approach is feasible and acceptable to healthcare providers and patients in a general practice that focuses on at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although Australia has been recognised for its leadership in HIV prevention, to our knowledge, opt-out HIV testing has never been explored in Australian general practice. Our previous study of Australian healthcare providers' views on opt-out HIV testing found that half of the participating GPs questioned the acceptability and feasibility of the approach (Leidel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…, ‘perceived susceptibility’ refers to health care providers' beliefs about the likelihood that their patients will get a disease . For example, some HCPs believe that they are able to select patients for HIV testing based on demographic information . Even though there is a low prevalence of HIV in Australia, the ability to select patients for testing is lacking.…”
Section: The Health Belief Modelmentioning
confidence: 99%
“…‘Perceived barriers’ are health care providers' negative beliefs about opt‐out HIV testing that could limit their willingness to adopt such an approach. For example, health care providers may assume that their patients are unwilling to be tested for HIV or that testing would lead to anxiety or stigma . Some health care providers may be concerned when opt‐out HIV testing is performed with abbreviated pre‐test counselling and simplified consent .…”
Section: The Health Belief Modelmentioning
confidence: 99%